Investigation of Toxoplasma gondii Seropositivity in Uludağ University Hospital between 2009-2016 - Oktay Alver; Melda Payaslıoğlu; Beyza Ener (Türkiye Parazitoloji Dergisi, 2019)

(untitled)
Objective:The aim of this study is to investigate the distribution of anti-Toxoplasma gondii immunoglobulin G (IgG) and immünoglobulin M (IgM) antibodies in patients with suspected toxoplasmosis admitted to the Practice and Research Center of Health of the Medical Faculty of Uludağ University.Methods:The blood samples examined for the presence of anti-T. gondii IgG antibody and anti-T. gondii IgM antibody by an enzyme linked fluorescent assay test, anti-T. gondii IgG avidity value was evaluated by VIDAS (BioMérieux, France) kit.Results:In our study, anti-T. gondii IgG seropositivity in 3311 (30.7%) of 10.603 cases and anti-T. gondii IgM seropositivity in 1423 (9.7%) of 14.618 cases were detected. Seropositivity of anti-T. gondii IgG was 37.5% in women of childbearing age group. The avidity value was high in 56.1% (n=156) and low in 28.9% (n=80) of childbearing age group women with positive anti-T. gondii IgG and anti-T. gondii IgM test.Conclusion:Especially in regions where seroprevalence is high, we think that pregnant women and women of childbearing age should be investigated in terms of T. gondii antibodies.